2019
DOI: 10.1002/lt.25424
|View full text |Cite
|
Sign up to set email alerts
|

Improved Graft Survival After Liver Transplantation for Recipients With Hepatitis C Virus in the Direct‐Acting Antiviral Era

Abstract: Highly effective direct‐acting antiviral (DAA) therapy has transformed outcomes of liver transplantation in hepatitis C virus (HCV) patients. We examined longer‐term outcomes in HCV‐positive recipients in the DAA era and analyzed the Scientific Registry of Transplant Recipients for primary adult, single‐organ, nonfulminant liver transplant recipients in the United States from January 1, 2008 to June 30, 2018. Graft loss was compared among HCV‐positive liver transplant recipients who received either an HCV‐nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 27 publications
0
67
0
Order By: Relevance
“…Even among these patients, the persistence of HCV infection post‐transplantation was associated with poor outcomes and led to worse post‐transplant survival . However, the advent of highly effective direct‐acting antiviral therapy (DAAs) has led to post‐transplantation HCV cure rates exceeding 95%, and with it, a negation of the ill effects of HCV previously seen in both LT and KT recipients . A number of clinical trials, along with data from the HCV‐TARGET cohort, have demonstrated the efficacy and safety of the use of these agents in the post‐transplant setting .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even among these patients, the persistence of HCV infection post‐transplantation was associated with poor outcomes and led to worse post‐transplant survival . However, the advent of highly effective direct‐acting antiviral therapy (DAAs) has led to post‐transplantation HCV cure rates exceeding 95%, and with it, a negation of the ill effects of HCV previously seen in both LT and KT recipients . A number of clinical trials, along with data from the HCV‐TARGET cohort, have demonstrated the efficacy and safety of the use of these agents in the post‐transplant setting .…”
Section: Introductionmentioning
confidence: 99%
“…Newer agents, including glecaprevir/pibrentasvir (GLE/PIB), have similarly been shown to be safe and efficacious . Indeed, recently published data derived from the Scientific Registry of Transplant Recipients (SRTR) suggest equivalent 1‐ and 3‐year survival among HCV‐infected patients undergoing LT …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] There is no denying that the use of DAAs in liver recipients with RHC or even kidney recipients with de novo HCV infection has largely mitigated this problem, enabling timely, safe and cost-effective viral eradication. 4,5,15 However, data on the utilization of DAAs post-transplant are limited when compared to the abundance of large and small, prospective and retrospective studies in immunocompetent patients. The introduction of all-oral, interferon-free DAAs into routine clinical practice is relatively recent (sofosbuvir/ ledipasvir attained Federal Drug Administration approval in October of 2014, with others following suit), and as such there is paucity of robust data on the SVR rates in DAA-and more specifically the NS5A-experienced OLT recipients with RHC.…”
Section: Discussionmentioning
confidence: 99%
“…Allograft re-infection by the hepatitis C virus (HCV) in treatment-naïve or unsuccessfully treated orthotopic liver transplant (OLT) recipients is swift and universal and used to be associated with an accelerated rate of fibrosis progression. [1][2][3] The advent of direct-acting antivirals (DAAs) dramatically changed the landscape of HCV treatment, with safe and effective regimens that have high cure rates leading to significantly improved outcomes in the post-OLT setting 4,5 Still, treatment of recurrent hepatitis C (RHC) in liver transplant recipients may pose a challenge. 6 As such, there remains the necessity to periodically restage the relatively few patients who either fail or are unable to tolerate DAA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…66,67 Cotter et al demonstrated that, in the DAA era, there has been an increase in the utilisation of HCV-viraemic donor livers, including into HCVnegative recipients, with good graft outcomes. 68 The use of DAAs has changed the landscape of HCV treatment and, annually, less patients with endstage liver disease due to HCV are listed for LT. [68][69][70][71][72][73][74] Living donor liver transplantation The most important intervention to increase the donor pool is living donor liver transplantation (LDLT). Initial results on LDLT for HCC indicated an increased risk of recurrence.…”
Section: Use Of Marginal Graftsmentioning
confidence: 99%